Metal-Free Catalyzed Defluorinative O-Arylation of Pyrazolones with Polyfluoroarenes - Yang, Liu; Qin, Tao; Liu, Bin (Synlett, 2023)
An efficient and general method for defluorinative O-arylation of pyrazolones has been successfully developed under metal-free conditions. This methodology allows for the synthesis of desired products by using a wide range of pyrazolones and polyfluoroarenes as starting materials. The compatibility of various substrates was demonstrated, ensuring the applicability of this method. Furthermore, the synthesis of the target compounds at a gram scale and the ability to perform late-stage modifications highlight the potential of this approach in preparative pharmaceutical synthesis and organofluorine chemistry.
Keywords: defluorinative; O-arylation; pyrazolones; polyfluoroarenes; metal-free